Development of Children's Literature Book Based on Primary School Students’ Ecoliteration - Hartati, Tatat; Andriani, Eli Nurlela; Supriatna, Nana; Nuriyanti, Risma (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
Lack of student interest in literature is due to the low literacy of students. Therefore, one of the ways to improve the students’ literacy and ecological awareness is through children's literature . Hence, Ecoliteration-based children's literature books are considered to be used as learning support books, media as well as sources of learning Bahasa for elementary schools .This study aimed to determine the design of eco-literation-based children's literature models for elementary school students.. This study adopted a development research wich Educational Design Research (EDR) was applied. This study involved lecturers, practitioners/ experts, and elementary school, teachers. The developed book contained some materials namely Bahasa, Science, and Social Sciences for four grade students by proposing a theme of " Peduli Terhadap makhluk Hidup (Caring for Sentient Beings)", added with Basic Competence from 2013 curriculum of Environmental Education lesson (PLH) and eco-literation competencies (Head, Heart, Hands, and Spirit). This study has 3 major findings: (1) the researchers successfully created a eco-literation-based children’s literature model book for elementary school pupils entitled “The Mystery of the Disappearance of A Friend” and “The Mystery of the Butterfly” (2) This study found the suitable characteristics of eco-literation book for Elementary School Students, (3) There are positive response towards these kinds of literature from the experts and the teachers.